The Implementation of the Application of Law of Criminal Acts with Violence - Dewi Indrasari; Siti Rodhiyah Dwi Istinah; Amin Purnawan (Universitas Islam Sultan Agung, 2022)
The purpose of this study is to determine the implementation of the application of the law of criminal acts with violence in the Demak District Court. The approach method used is normative legal research which is descriptive analytical in nature with legal research that is carried out by examining library materials or secondary data as the basic material for research. Conclusions in the defendant's research in the decision of the judges of the Demak District Court sentenced to imprisonment for 1 (one) year 4 (four) months and pay court fees in the amount of IDR 3,000 (three thousand rupiah).The sanctions imposed by the Panel of Judges on the defendant are too light, in Article 365 of the Criminal Code the maximum period of time the defendant can be snared is 9 (nine) years.